Slot Antenna With Non-Foster and Negative Conductance Matching in Consecutive Bands - Chen, Hsiao-Chin; Yang, Hong-Yi; Kao, Chia-Chun; Ma, Tzyh-Ghuang (IEEE antennas and wireless propagation letters, 2019)
An active slot antenna integrated with a negative impedance converter (NIC) having non-Foster and negative conductance matching in consecutive bands is proposed and experimentally validated in this letter. The key innovation is the new NIC design to maximize the antenna bandwidth by using different operation principles in different bands. In the non-Foster matching region at lower frequencies, the bandwidth is widened at a sacrifice of the efficiency due to parasitic loss of the NIC, while in the active region at higher frequencies, the gain, efficiency, and bandwidth are dramatically boosted thanks to the negative conductance sourced by the NIC. The stability is confirmed, and the antenna performance is experimentally verified. The design guideline is carefully explained as well.